Renewable Energy and its Moderation on Green Home Selection in Indonesia: Bridging Environment, Product, and Value - Napitupulu, Junika; Siahaan, Septony B.; Sitorus, Sunday Ade (International Journal of Energy Economics and Policy, 2023)
This study aims to investigate the moderating role of renewable energy on sustainable environmental factors, environmentally friendly products, and customer value in consumer decision making in choosing a residential house without greenhouse effect in Indonesia. The data source in this study is 270 people who have a residence without a greenhouse effect. The research method is a quantitative descriptive method using Structural Equation Model data analysis using the PLS 3.0 application. The population in this study amounted to 270 people who have a residence without a greenhouse effect, while the number of samples was 270 people who have a residence without a greenhouse effect with a sampling technique using the census method, while the data collection technique was carried out using observation, questionnaires and documentation studies. The results of this study indicate that consumers tend to be more interested in choosing residential houses that use renewable energy and have environmentally friendly features. In addition, customer values perceived by consumers, such as quality, price, comfort, and safety, also have a positive influence on consumer decisions in choosing residential houses without greenhouse effect. Limitations of this study include the use of self-reporting survey data, which may affect the validity and reliability of the results. In addition, this study focused on the context of residential homes in Indonesia, so generalizability of the findings needs to be considered with caution. Recommendations for future research include involving a more representative sample, incorporating objective data to measure environmental variables and environmentally friendly products, and expanding the geographical scope of the study to compare results between different regions in Indonesia.